PERANCANGAN SISTEM INVENTORY MATERIAL PADA PERSIAPAN PROYEK PERGUDANGAN PT NUSA SUKSES JAYA - Kurniawan, Ricky; Setyarini, Ririen (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
Out of all business company process using technology and one of them is inventory. By combining the process of inventory company business with technology, it will make a great contribution to the company itself. Which is one of the benefits is the managerial in the inventory management of the company. In the meant time, the company who use this inventory method by replacing the old and traditional one with the new one integrated with the information system, will reach the maximal effort of working in the company and will save a lot of time in terms of managing the inventory of company. Comparing between the two systems of the company, the old one and the new integrated one, of course the most updated one will be good and be implemented in almost all of the company in the world The change in the company system was conducted on PT. Nusa Sukses Jaya. The changes include replacing the system with the new one integrated by information system in order to answer the challenge of growing technology in the modern age. Key words Perusahaan, the old system, the new integrated system, inventory